U.S. transportation infrastructure resilience: Influences of insurance, incentives, and public assistance. (January 2021) - Tonn, Gina; Reilly, Allison; Czajkowski, Jeffrey; Ghaedi, Hamed; Kunreuther, Howard
Abstract: The U.S. economy and way of life are highly dependent on transportation systems, which move goods and people locally, regionally, nationally, and internationally. Major disruptions to transportation networks due to natural hazards, manmade hazards (notably terrorist and cyberattacks), accidents, or infrastructure failure can cause substantial social and economic impacts. Through qualitative and quantitative analyses, including an in-depth review of the literature and semi-structured interviews, we identify barriers to and opportunities for lowering transportation-related disaster losses and for improving infrastructure risk management including the need for better data and metrics to support resilience. Our analyses are supported by a review of transportation-related Public Assistance (PA) expenditures to understand the magnitude and variation of expenditures over time. PA is a U.S. Federal Emergency Management Agency (FEMA) program dedicated to partial reimbursement of hazard-related losses for public infrastructure. Our analyses show that the availability and significant outlays of PA after disasters inhibit risk-based loss reduction actions by infrastructure managers. Risk management tools, notably insurance and mitigation measures, can efficiently reduce disaster losses and speed recovery times. This paper concludes with recommendations for policy measures to facilitate improvements in transportation infrastructure resilience. Highlights: Almost $10 billion federal disaster assistance for transportation (2003–2017). Availability of public funds for restoration reduces loss reduction activities. Insurance and mitigation measures reduce disaster losses and speed recovery time. Need for data, metrics, study of emerging risks, tools for resilience financing. Study developed seven recommendations for enhancing infrastructure resilience.